Price-Output Uncertainty and Allocative Efficiency: An Empirical Study of Small-Scale Farms - Wu, Craig C. (The Review of Economics and Statistics, 1979)
IT has long been suspected that price uncertainty may cause allocative inefficiency in farm operation.' This may be especially true for small farms since they cannot afford expert economic advice (Schultz, 1964, p. 118). It is also a common understanding that output uncertainty may reduce allocative efficiency.2 Therefore, if prices and output are known with less uncertainty, farmers should allocate their resources more efficiently. This study is intended to investigate empirically such a relation.3 The data are for the small-scale family farms of Taiwan in the mid-sixties drawn from three mixed farming regions of the island.4 Most of the family farms of Taiwan grow rice alongwith other crops. The extent to which a farm is engaged in rice farming may be measured by a ratio of rice income to total crop income, to be referred to as the rice income ratio. Due to government price stabilization policies on rice, rice prices have been the most stable among almost all crops.5 The unit yield of the rice crop had also increased rather steadily before 1967 while that of other crops showed much larger year to year variations.6 Rice farming in Taiwan thus involves less price and output uncertainty than other crops. It seems reasonable to assume that a farm with a larger rice income ratio is involved in a lesser extent of price and output uncertainty and the variable rice income ratio can be used as a proxy of the degree of price and output certainty facing each farm. When this variable is related to allocative efficiency, it is therefore expected to have a favorable effect on the latter due to less price and output uncertainty.